2015
DOI: 10.4238/2015.july.28.21
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-6 gene -174G>C polymorphism and chronic obstructive pulmonary disease risk: a meta-analysis

Abstract: ABSTRACT. Association studies of interleukin-6 (IL-6) -174G>C polymorphism and chronic obstructive pulmonary disease (COPD) have yielded inconsistent results, possibly because single studies often lack sufficient statistical power. A comprehensive search was performed in the PubMed, Embase, Elsevier, Web of Science databases, Wanfang, and the Chinese National Knowledge Infrastructure (CNKI) databases for published studies investigating the associations between IL-6 -174G>C polymorphism and COPD. Odds ratios (O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…This was surprising given reports of increased levels of sIL-6R in people with COPD (15), and previous reports of associations of polymorphisms in the IL-6 gene with this condition (16,27,28). Recent experimental evidence in mouse models supports the involvement of IL-6 trans-signaling in the development of emphysema via activation of the mammalian target of rapamycin complex 1 (mTORC1) pathway and that this is independent of the inflammatory response (29).…”
Section: Discussionmentioning
confidence: 78%
“…This was surprising given reports of increased levels of sIL-6R in people with COPD (15), and previous reports of associations of polymorphisms in the IL-6 gene with this condition (16,27,28). Recent experimental evidence in mouse models supports the involvement of IL-6 trans-signaling in the development of emphysema via activation of the mammalian target of rapamycin complex 1 (mTORC1) pathway and that this is independent of the inflammatory response (29).…”
Section: Discussionmentioning
confidence: 78%
“…It is reported that the gene polymorphisms of inflammatory cytokine could affect cytokine mRNA transcription and thus change the serum levels of inflammatory cytokine (Larcombe et al, 2005). In the recent studies, emphasis often be focused on investigating the role of IL-6 polymorphisms to several kinds of diseases, such as chronic obstructive pulmonary disease, cardiovascular disease, HBV-related liver disease, or osteoporosis (Chang et al, 2015;Xie et al, 2015;Buraczynska et al, 2016). In our study, we carried out a study to investigate the role of IL-6 polymorphisms in the risk of CAD, and we revealed that the IL-6 -174G/C genomic polymorphism was correlated with an elevated risk to CAD in multiple genetic models.…”
Section: Discussionmentioning
confidence: 99%
“…The IL-6 gene, located at chromosome 7p21-24, is composed of 4 introns and 5 exons. Since single nucleotide polymorphisms of IL-6 gene promoter may affect the expression and secretion of IL-6, and subsequently the altered circulating levels might result in relevant biological responses, and the IL-6 polymorphism has been regarded as a crucial modulator in pathogenesis of various diseases, including Alzheimer's disease, type 2 diabetes, celiac disease, chronic obstructive pulmonary disease and osteoarthritis (de Albuquerque Maranhão et al, 2015;Fernandes et al, 2015;Xie et al, 2015;Buraczynska et al, 2016;Ramos Dos Santos et al, 2016). Although several studies have shown that IL-6 polymorphisms could be also involved in the development of CAD, the conclusions were not consistent Liu et al, 2015;Wang et al, 2015;Yang et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The IL6 gene, which has the chromosomal locus 7p21, spans 5 kb and contains four introns and five exons. The best characterized genetic variant of IL6 is a G-to-C substitution at position -174 in the promoter region of IL6 (-174 G/C or rs1800795), upstream of the transcription start site, which influences IL-6 levels in vitro and in vivo (Belluco et al, 2003;Jin et al, 2015;Xie et al, 2015;Yang et al, 2015). Because the -174 G/C polymorphism of IL6 increases IL-6 expression, it may be associated with susceptibility to MI.…”
Section: Introductionmentioning
confidence: 99%